Variable pricing as a load management strategy - Hassan, Ismail (Faculty of Electrical Engineering, 1993)
Variablepricing ojelectricity is introduced as a strategy that can achieve the desired benefits ojload management and efficient rates design. The utility gains by optimal allocation and efficient utilisation oj resources and substantial savings in capital investments and as a result the customer should pay less in electricity bills. Ideal priting however must be compromised with the needfor practical rate structures. In the final analysis the success oj the strategy depends a great deal on correct customer response. Keywords: Load management, variable pricing, spot pricing, dynamic pricing, optimal allocation and efficient utilisation ojresources, time-of-use rates, merit order, loadfartor, marginal cost, prescribed pricing